Anne's house of dreams - Montgomery, L. M. (New York : Bantam Books, 1972)
Anne of Green Gables, the orphan girl who lives on Price Edward Island, experiences romance as she begins her years of young adulthood
Keywords: Marriage -- Fiction; Friendship -- Fiction; Prince Edward Island -- Fiction